2012
DOI: 10.2217/nmt.11.81
|View full text |Cite
|
Sign up to set email alerts
|

Development of Guidelines for Occupational Therapy in Huntington’s Disease

Abstract: This paper introduces the 'Guidelines for Occupational Therapists working with people with Huntington's disease' which is currently being developed by the European Huntington's Disease Network (EHDN) Standards of Care Occupational Therapists working group. This article aims to describe the everyday functional problems experienced by people with Huntington's disease, the role of the occupational therapist, the systematic literature review which preceded the formulation of the guidelines and use excerpts from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
7
0
5
Order By: Relevance
“…An Occupational Therapist (OT) will seek to address the multiple facets of HD which strengthen or hinder the person’s performance in any of their activities of daily living (ADL) throughout their life span at a personal, environmental, and occupational level. As with many of the professions crucial to the success of MDT working in HD care, the scientific evidence documented for the outcomes of OT is sparse, but the value and scope of OT are acknowledged [ 44 ] with clear illustrations of the importance of assessing the functional manifestation of HD by Cook et al [ 45 ] and the consequences of not. Best practice guidelines were produced in 2012 to establish a standard of care, and from this summary, guidance is in the form of clinical tips (hda.org.uk).…”
Section: Clinical Managementmentioning
confidence: 99%
“…An Occupational Therapist (OT) will seek to address the multiple facets of HD which strengthen or hinder the person’s performance in any of their activities of daily living (ADL) throughout their life span at a personal, environmental, and occupational level. As with many of the professions crucial to the success of MDT working in HD care, the scientific evidence documented for the outcomes of OT is sparse, but the value and scope of OT are acknowledged [ 44 ] with clear illustrations of the importance of assessing the functional manifestation of HD by Cook et al [ 45 ] and the consequences of not. Best practice guidelines were produced in 2012 to establish a standard of care, and from this summary, guidance is in the form of clinical tips (hda.org.uk).…”
Section: Clinical Managementmentioning
confidence: 99%
“…Although there is general agreement that comprehensive, multidisciplinary care is needed [ 4 , 19 , 21 24 ], the complex and changing clinical picture may be a challenge for health professionals. Standards of care, aimed at separate groups of healthcare professionals (i.e., speech and language therapists) have been published, with the purpose of being a foundation for further research and evaluation of provided care [ 18 , 25 , 26 ]. A few clinics adapting comprehensive care models have emerged in the US, Australia and Europe [ 4 , 24 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, a guide developed by occupational therapists who worked with patients with HD concluded that one of the most frequent problems of these patients was related to activities that involved manual tasks such as eating, fastening buttons, and writing. This is due to reduced manual dexterity, poor coordination, and reduced grip (Cook et al, 2012). Other studies based on the COPM have also identified self-care as the category, including most occupational difficulties (McColl et al, 2006).…”
Section: Discussionmentioning
confidence: 99%